2022
DOI: 10.6007/ijarbss/v12-i8/14478
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Attributes and Entrepreneurial Intention among Hospitality Students in Malaysian Higher Education Institutions: An Educational Approach

Abstract: The effects of the COVID-19 pandemic on the employability of recent graduates is one of the primary worries expressed by academics. However, assessing the entrepreneurial qualities among undergraduate students seems like an initial effort that may enhance career opportunities and marketability. Given the significance of entrepreneurship to a nation's economic growth, it's crucial to begin instilling entrepreneurial values from a young age which can lead to the readiness to become an entrepreneur for employment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
(61 reference statements)
1
0
0
Order By: Relevance
“…The fact that several of their seniors they know have successfully launched their own businesses and are succeeding served as a source of motivation for them. This finding corroborates with Fadzil et al (2022) who observed that hospitality operators that have established enterprises are considered successful entrepreneurs.…”
Section: Discussionsupporting
confidence: 91%
“…The fact that several of their seniors they know have successfully launched their own businesses and are succeeding served as a source of motivation for them. This finding corroborates with Fadzil et al (2022) who observed that hospitality operators that have established enterprises are considered successful entrepreneurs.…”
Section: Discussionsupporting
confidence: 91%